A dynamic collimation system for penumbra reduction in spot‐scanning proton therapy: Proof of concept. Issue 9 (5th August 2014) - Hyer, Daniel E.; Hill, Patrick M.; Wang, Dongxu; Smith, Blake R.; Flynn, Ryan T.
Abstract : Purpose: : In the absence of a collimation system the lateral penumbra of spot scanning (SS) dose distributions delivered by low energy proton beams is highly dependent on the spot size. For current commercial equipment, spot size increases with decreasing proton energy thereby reducing the benefit of the SS technique. This paper presents a dynamic collimation system (DCS) for sharpening the lateral penumbra of proton therapy dose distributions delivered by SS. Methods: : The collimation system presented here exploits the property that a proton pencil beam used for SS requires collimation only when it is near the target edge, enabling the use of trimmers that are in motion at times when the pencil beam is away from the target edge. The device consists of two pairs of parallel nickel trimmer blades of 2 cm thickness and dimensions of 2 cm × 18 cm in the beamˈs eye view. The two pairs of trimmer blades are rotated 90° relative to each other to form a rectangular shape. Each trimmer blade is capable of rapid motion in the direction perpendicular to the central beam axis by means of a linear motor, with maximum velocity and acceleration of 2.5 m/s and 19.6 m/s 2, respectively. The blades travel on curved tracks to match the divergence of the proton source. An algorithm for selecting blade positions is developed to minimize the dose delivered outside of the target, and treatment plans are created both with and without the DCS. Results: : The snout of the DCS has outer dimensions of 22.6 × 22.6 cm 2 and is capable of delivering a minimum treatment field size of 15 × 15 cm 2 . Using currently available components, the constructed system would weigh less than 20 kg. For irregularly shaped fields, the use of the DCS reduces the mean dose outside of a 2D target of 46.6 cm 2 by approximately 40% as compared to an identical plan without collimation. The use of the DCS increased treatment time by 1–3 s per energy layer. Conclusions: : The spread of the lateral penumbra of low‐energy SS proton treatments may be greatly reduced with the use of this system at the cost of only a small penalty in delivery time.